Interdisciplinary Text Studies: Structure and Discourse Analysis Approach - Afandi, Akhmad Jazuli (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
The study of text is crucial for comprehending scientific disciplines. The primary focus of interdisciplinary text studies is to gain insights into texts in a cross-disciplinary manner. Analyzing structure and discourse allows exploring analytical tools and concepts relevant to both fields, making them useful in interdisciplinary texts. This research utilizes qualitative methods and a library approach using structure and discourse analysis. The data collected will be presented in a descriptive-analytical manner. The study aims to bridge the gaps in text and provide various approaches to analyzing text. The analysis of discourse and structure is closely linked to how we analyze scientific, social, and other phenomena and is dependent on the language and text used. The text structure can be understated implicitly, textually, or contextually, depending on the needs of each scientific discipline. The results demonstrate that structure can be a helpful tool for interdisciplinary text studies and valuable paying attention to structural systems, cohesion, and applying syntactic, semantic, and pragmatic study. Discourse analysis can also be helpful if the texts studied are analyzed about discursive practices and other relevant knowledge.